2012
DOI: 10.1053/j.gastro.2012.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Igf2bp1 Is Required for Full Induction of Ptgs2 mRNA in Colonic Mesenchymal Stem Cells in Mice

Abstract: Background & Aims Prostaglandin-endoperoxide synthase (Ptgs)2 is an enzyme involved in prostaglandin production during the response to mucosal damage. Its expression is regulated, in part, by mRNA-binding proteins that control the stability of Ptgs2 mRNA. We used a precise system of colonic injury and repair to identify Ptgs2 mRNA-binding proteins. Methods We used endoscopy-guided mucosal excision to create focal injury sites in colons of mice. Wound beds from wild-type, Ptgs2−/−, Ptgs2+/−, and Myd88−/− mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(96 citation statements)
references
References 34 publications
4
88
0
3
Order By: Relevance
“…This was not an immediate consequence of injury, as α-SMA loss occurred 6 days after biopsy injury (14). In our previous study, coadministration of two stable prostaglandin analogs of PGE 2 and PGI 2 prevented loss of staining in the muscularis propria of mucosally injured Ptgs2 -/-mice (14). Here, we determined that PGI 2 was the critical prostaglandin for smooth muscle protection after mucosal injury.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…This was not an immediate consequence of injury, as α-SMA loss occurred 6 days after biopsy injury (14). In our previous study, coadministration of two stable prostaglandin analogs of PGE 2 and PGI 2 prevented loss of staining in the muscularis propria of mucosally injured Ptgs2 -/-mice (14). Here, we determined that PGI 2 was the critical prostaglandin for smooth muscle protection after mucosal injury.…”
Section: Resultsmentioning
confidence: 62%
“…We previously showed that colonic mucosal injury of Ptgs2 -/-mice led to penetrating ulcers, as highlighted by loss of α-smooth muscle actin (α-SMA [Acta2]) staining within the underlying muscularis propria (Figure 1, A and B). This was not an immediate consequence of injury, as α-SMA loss occurred 6 days after biopsy injury (14). In our previous study, coadministration of two stable prostaglandin analogs of PGE 2 and PGI 2 prevented loss of staining in the muscularis propria of mucosally injured Ptgs2 -/-mice (14).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…We hypothesize that innate stimulation-driven Tpl2-mediated Cox-2-PGE 2 expression in IMFs is part of an on/off switch mechanism conditionally activated to support crypt function under emergency conditions enhancing stem/progenitor cell survival and/or proliferation. Relevantly, a PGE 2 -expressing population identified to be mesenchymal stem cells but not myofibroblasts (50) shows defective repositioning close to crypts in the rectum of DSS-treated Myd88 −/− mice but not altered Cox-2 expression (30). However, the exact relationship between this population, intestinal fibroblasts, and myofibroblasts is not completely clear (51).…”
Section: Discussionmentioning
confidence: 99%